Glucocorticoid withdrawal in systemic lupus erythematosus: are remission and low disease activity reliable starting points for stopping treatment? A real-life experience. Issue 2 (11th June 2019) - Tani, Chiara; Elefante, Elena; Signorini, Viola; Zucchi, Dina; Lorenzoni, Valentina; Carli, Linda; Stagnaro, Chiara; Ferro, Francesco; Mosca, Marta
Abstract : Objectives: To evaluate the proportion of patients who have successfully withdrawn glucocorticoids (GCs) in a longitudinal cohort of patients with systemic lupus erythematosus (SLE) over a period of 6 years; to evaluate patient characteristics during GC withdrawal in relation to existing definitions of remission and Lupus Low Disease Activity State (LLDAS); and to evaluate the occurrence of flares after GC withdrawal. Methods: Patients who attempted GC withdrawal were identified for the cohort, and the following information was assessed during withdrawal attempts: date of last disease flare, disease activity and damage and ongoing treatment. Information regarding the occurrence of disease flares after GC withdrawal was also recorded for patients who successfully stopped treatment. Definitions of remission were applied to GC withdrawal in line with European consensus criteria (Definitions of remission in SLE [DORIS]) and LLDAS in line with the Asian Pacific Lupus Consortium definition. Results: 148 patients were involved in the study; GC withdrawal was attempted in 91 patients (61.5%) with 77 patients (84.6%) successfully stopping GCs. At the beginning of the GC reduction, the majority of patients were in complete or clinical remission (48.9% and 39.6%, respectively). Disease activity was significantly lower in patients who successfully stopped GCs, and the proportion of patients in complete remission was higher (54.2%) with respect to patients who failed in their attempt. Among patients who stopped GCs, 18 flares were recorded after a median of 1 year. The time period since the last flare was shorter in patients who experienced flares with respect to patients who did not flare (mean 0.93 years vs 6.0, p<0.001). Conclusions: GC withdrawal is an achievable goal in SLE and may be attempted after a long-term remission or LLDAS to protect the patient from disease flares.